Keterjaminan Kedudukan Dzaul Arham Dalam Kewarisan Islam Melalui Wasiat Wajibah - Laras Shesa (AL-ISTINBATH : Jurnal Hukum Islam, 2018)
Dzaul Arham mentioned his part in the discussion of the obligatory will. Mandatory wills are different from ordinary testaments. Although the boundaries of the section are the same, they cannot be one third. But regarding its position there are still differences of opinion. And according to the author although with the existence of differences of opinion that little or no part of dzaul arham was taken into account. In this journal the author uses substantive qualitative research methods, with the research type library research. The primary data comes from the literature. With the method of deductive analysis, something universal leads to a specific direction. The position of dzaul arham is indeed not written in the Koran but its position has become the ijma of the ulamas still being calculated with several conditions including no furudh ashhabul. Second, there is no ashabah. And finally, if furudh ashhabul only consists of a husband or wife, then he will receive his inheritance fardh, and the rest will be given to dzawul arham. Through the obligatory dzaul arham testament as though the parts are taken into account. And the completion of the obligatory will that the writer recommends is a settlement from Hasbi Ash-Shiddiqi, namely by determining the part of each heir including the recipient of the obligatory will, replacing the position of his deceased parents according to the level of his acceptance. Providing the recipient of the mandatory will for the portion that should have been received by his parents a maximum of one third of the portion. Giving excess balance after taking the mandatory test taker to the heirs according to the level of their respective parts. So that this way the dzawul arham part is still very calculated, or its position can be guaranteed.